Bridge scour monitoring by using RFID system - Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, M. Z. (2014)
Bridge scour is an erosion which removes stream bed or bank material from bridge foundation due to flowing of water. Too much bridge scour is risky for the bridge foundation and causes sudden bridge to collapse without any warning. It implements significant impacts on the traveling public safety as well as the economy of the country. A number of parameters are associated with scour, thus different types of sensors are required to measure the individual affecting factor. A complex and expensive data logging from sensor and electronic communication systems are used to monitor the bridge scour in real-time to ensure the integrity of bridge structure. A high frequency band (13.56MHz) radio frequency identification (RFID) system has been proposed and that has been validated by simulation using PSpice software for direct scour monitoring scheme, which is simple and low-cost. A number of passive RFID tags have been piled surrounding the bridge foundation which are continually detected by the FRID reader. The erosion of the river bed carries out the RFID tag from nearby the bridge structure. As a result, the RFID reader can directly detect the absence of the tags as well as the amount of the scouring. Since, the design structure of the RFID system is simple, it is highly robust and easy to implement. The system can easily be implemented with an existing bridge structure and a wireless telemetry can be used to send the real-time data from the proposed system to a desktop computer in the monitoring lab.